2017
DOI: 10.1097/qai.0000000000001300
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anal HPV and Anal Dysplasia in HIV-Infected Women From Johannesburg, South Africa

Abstract: BACKGROUND Anal cancer is a relatively common cancer among HIV-infected populations. There are limited data on the prevalence of anal high-risk human papillomavirus (HR-HPV) infection and anal dysplasia in HIV-infected women from resource-constrained settings. METHODS A cross-sectional study of HIV-infected women age 25–65 recruited from an HIV clinic in Johannesburg, South Africa. Cervical and anal swabs were taken for conventional cytology and HR-HPV testing. Women with abnormal anal cytology and 20% of wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
(31 reference statements)
3
17
1
Order By: Relevance
“…For HRA to be successful as a cancer prevention strategy, it needs to be both effective and tolerable to the target patient population. While previous studies have examined the clinical utility and performance of HRA , few have documented patient experience with HRA, including the tolerability of discomfort during the procedure and postprocedure pain, as well as patient willingness to undergo routine or follow‐up HRA .…”
Section: Introductionsupporting
confidence: 91%
“…For HRA to be successful as a cancer prevention strategy, it needs to be both effective and tolerable to the target patient population. While previous studies have examined the clinical utility and performance of HRA , few have documented patient experience with HRA, including the tolerability of discomfort during the procedure and postprocedure pain, as well as patient willingness to undergo routine or follow‐up HRA .…”
Section: Introductionsupporting
confidence: 91%
“…Regarding clinical variables, HIV viral load and low CD4 counts were significantly associated with HR-HPV and multiple infections, which could raise the risk of persistent infection and consequently, of malignant development. Our result showed that HAART therapy was protective for multiple HPV infection, and it was previously demonstrated that HR-HPV prevalence was lower in patients in the long-term application of HAART [ 39 , 40 ]. However, the incidence of HPV-induced lesions in the anal canal are still high in patients on a program of HAART [ 41 ], and the frequency of anal cancer was no different in the pre-HAART and HAART eras [ 42 ].…”
Section: Discussionsupporting
confidence: 65%
“…The 2016 International Guidelines for Practice Standards in the Detection of Anal Cancer Precursors proposes a quality assurance metric: >90% of patients with cytologic HSIL should have hHSIL detected on HRA [23]. In other studies, the proportion of study participants having hHSIL detected in association with cytology anal HSIL was 67% (73/109) in Machalek et al [24], 52% (11/21) (with ASC-H included as HSIL cytology) in Heard et al [13], and 35% (6/17) (with ASC-H included as HSIL cytology) in Goeieman et al [14]. In addition, we found that random biopsies of the anal canal in our cohort of HIV-infected women did not add significantly to the detection of anal hHSIL (2/69 [3%]).…”
Section: Discussionmentioning
confidence: 78%
“…Heard et al [13] performed HRA on all patients and detected histologic HSIL in 6.4% (11/171) of their cohort. Studies of HIV-infected women in which only women with abnormal anal cytology underwent HRA found rates of anal hHSIL ranging from 4% to 9% [14][15][16][17][18][19]. The largest reported cohort by Gaisa et al found that of 795 HIV-infected women undergoing anal cancer screening with anal cytology, 39% of anal cytology specimens were abnormal; however, only 50% of the women with abnormal anal cytology underwent HRA [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation